Technologies for gas and condensate collection and preparation - Burova, M. Y.; Yatskevich, О. О.; Varavina, О. P. (National Technical University "Kharkiv Polytechnic Institute", 2025)
The manual contains a course on discipline «Technologies for gas and condensate collection and preparation». The manual provides a holistic, systematic understanding of the current state of the systems for collection and preparation of well products of gas and gas condensate fields for further transport. Intended for students of bachelor educational level of specialty 185 «Oil and gas engineering and technology».
Keywords: training manual; purpose of the gas collection system; well product accounting; compressing; natural gases; separation; filters; multi-stage degassing; physical absorption